2021
DOI: 10.1115/1.4052964
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Characteristics and Load-Sharing of Point-Contact Interface in Three-Body Mixed Lubrication

Abstract: The third particle occurred at the interface of contacting surfaces is common situations in relative motion part. This study involved developing an analysis framework to investigate the contact characteristics in the full range of 3-body mixed lubrication. Conventional 2-body mixed lubrication is a special case of 3-body mixed lubrication analysis with particle size of zero. This study revealed that the values of real contact area, film thickness, contact mode, and the solid contact load in 3-body contact were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In 2015, Wu et al [33] analyzed the peak contact temperature of rough surfaces under 3-body contact, but did not consider the transition mechanism of various 3-body contact modes and the change of micro-asperity deformation. Horng et al [34] combined contact mechanics and lubrication theory to study the mixed lubrication properties at 3-body interfaces. They show that the conventional film parameter (λ) was not a sufficient indicator of various lubrication regimes in 3-body contact.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Wu et al [33] analyzed the peak contact temperature of rough surfaces under 3-body contact, but did not consider the transition mechanism of various 3-body contact modes and the change of micro-asperity deformation. Horng et al [34] combined contact mechanics and lubrication theory to study the mixed lubrication properties at 3-body interfaces. They show that the conventional film parameter (λ) was not a sufficient indicator of various lubrication regimes in 3-body contact.…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Mechanical Engineering frontiersin.org concentration on the characteristics of the 3-body lubrication interface. Horng et al (2022) also noted that film parameter is not a suitable indicator for distinguishing lubrication regimes in 3body contact systems. Various operating conditions influence TPCA in 3-body dry contact conditions (Chern et al, 2022).…”
Section: Property Valuementioning
confidence: 99%
“…The 3-body dry contact model can be employed to calculate the relationship between the real contact area, surface separation, and the normal load. The normal load of solid, F s , and total contact area of solid, A t , are given by the following equations for the 3-body micro-contact model (Horng et al, 2022): Dimensionless area of dry contact vs. dimensionless normal load at various particle diameters: (A) contact area ratio of particle and (B) dimensionless total contact area for σ = 100 nm and η a = 10 11 m -2 .…”
Section: -Body Microcontact Analysismentioning
confidence: 99%
“…In the third body mechanism, the ZnO NPs function as nano ball bearings, effectively transferring sliding friction into rolling friction and reducing the real contact pressure, resulting in low friction and wear. 47,54 Thus, the anti-wear mechanism of IL remains unchanged while the role of NPs switches from the most tribofilm formation to the most nano bearing effect in the hybrid nanolubricant R + IL + ZnO. Several studies have pointed out that ZnO NPs exhibited different wear mechanisms according to the base oil.…”
Section: Film Thicknessmentioning
confidence: 99%
“…[42][43][44] The size and concentration of NPs play a crucial role in altering the contact characteristics, friction, and wear performance of lubricants. [45][46][47] Recently, ILs and NPs have been used as hybrid additives to enhance the tribological performance and limit environmental harmful compounds from existing commercial lubricants. Sabarinath et al 8 showed that the combination of SiO 2 NPs and an imidazolium-based IL in sesame oil exhibited excellent tribological properties.…”
Section: Introductionmentioning
confidence: 99%